Debt Policy of the Russian Regions : Economic and Legal Research - Gurinovich, Alexander G.; Smirnikova, Julia L. (Indian Journal of Finance, 2021)
This paper examined the actual problem of regional development – the development of priority directions of the Russian Federation constituent entities’ debt policy. The analysis of existing approaches in the definition of debt policy was carried out, and the application of a comprehensive economic and legal approach in conducting this study was argued. Methodological research tools included methods for processing statistical data obtained from official information of the Ministry of Finance of the Russian Federation on the volumes and composition of the public debt of the constituent entities of the Russian Federation. The indicators characterizing the level of the debt burden of the subjects of the Russian Federation – the volume and structure of public debt – were analyzed. The ranking on the volume of public debt was carried out according to indicators of the constituent entities of the Russian Federation included in federal districts. The ranking on the structure of public debt was carried out based on the type of debt obligations. Based on the data obtained, regions with the highest debt load were identified. The legal mechanisms of public debt management, used to reduce the debt burden, were analyzed. The analysis of the debt policy elements showed main problems with strategy, debt management, and control from the regional legislative point of view. Recommendations were proposed for development of determining the debt policy of regions in financial program documents of the constituent entities of the Russian Federation.